Pine and eucalypt litterfall in a pine-invaded eucalypt woodland: The role of fire and canopy cover - Williams, Moira C.; Wardle, Glenda M. (Forest ecology and management, 2007)
The accumulation of considerable amounts of litter within Pinus populations can have adverse effects on litter fauna and native plant recruitment. In this two year study, we quantified Pinus radiata and Eucalyptus spp. litterfall in a eucalypt woodland invaded by pines. In the most heavily invaded areas pine basal area reached 11.3 m 2/ha and produced a mean annual litterfall rate of more than 1400 kg/(ha year) (dry weight) directly underneath the pine canopy, implying that in the latter stages of invasion wildling populations are capable of producing considerable amounts of pine litter. The significant positive relationship between P. radiata basal area and litterfall ( r = 0.861; p = 0.028) indicates that pine basal area is a good indicator of the area of land within an invaded area subject to direct litter impacts. Clumped adult pines results in heavy litter fall on a small area of land whereas uniformly spaced trees leads to uniformity of litterfall with lighter impacts. The majority of pine litter (>70%) fell directly below the pine canopy suggesting that most effects of litter will be restricted to these areas. Wildfire reduced litterfall from the trees that survived by 61% and 28% for pine and eucalypt, respectively, suggesting that any potential adverse consequences of pine litter will be reduced for several years following fire. In areas invaded by pines the addition of large amounts of highly flammable pine litter may increase the fire risk to the plantation resource.